Risk of incidental genital tract malignancies at the time of myomectomy and hysterectomy for benign conditions - Garima Yadav; Meenakshi Rao; Shuchita Batra Goyal; Pratibha Singh; Priyanka Kathuria; Meenakshi Gothwal (Korean Society of Obstetrics and Gynecology, 2021)
Objective To determine the incidence of accidentally diagnosed genital malignancies in women undergoing gynecological surgeries for pathologies presumed to be benign. Methods Data of all women who underwent hysterectomy for benign indications were retrieved from hospital records. A total of 628 cases of hysterectomy and 35 cases of myomectomy were included. The final histopathology was accessed through the computer records, and the total number of genital tract malignancies was included. Results The incidence of occult uterine, ovarian, and cervical malignancies in women undergoing hysterectomy was 0.47%, 0.31%, and 0.15%, respectively. The incidence of uterine corpus malignancies in women undergoing myomectomy was 2.8%, and 3 cases of smooth muscle tumor of uncertain malignant potential (STUMP) were also identified. Endometrial stromal sarcomas were the most common pathology among uterine malignancies, followed by leiomyosarcoma and endometrial adenocarcinoma. Conclusion Postoperative diagnosis of malignancies in women undergoing surgery for benign indications poses great challenges to the treating surgeon. Occult malignancies must be ruled out by thorough preoperative assessment, especially in some subsets of women. Morcellation is an inevitable technique and complement to laparoscopic surgeries, although little chances of malignancy spread is related to its use. Nevertheless, thorough preoperative investigations and always ensuring contained morcellation can minimize these chances.